Methodological Aspects of the Dynamics of Legal Relationships as a Social and Legal Phenomenon - Vershok, I. L. (Sibirskoe ûridičeskoe obozrenie (Online), 2021)
The article is devoted to the study of legal relationship as a phenomenon that exists in two modes of being of law: legal reality and legal validity. Classical approaches to the definition of a legal relationship as a social relationship regulated by law are criticized. The understanding of the legal relationship as a result of the implementation of legal norm is also criticized. It is recognized that these approaches do not fully provide a scientific characteristic of legal relationships as a social and legal phenomenon. Instead of the usually distinguished elements of a legal relationship in the form of a subject, object and content, it is proposed to study its dynamic parameters. The dynamics of a legal relationship is considered as a result of the intentionality of the legal consciousness of its subject. In legal reality, a legal relationship is studied as a social action in the conditions of adaptation of the subject to the environment. This legal relationship is due to the general normativity of biological, social and technical origin. The vital normativity of legal reality is considered as a determinant of legal relations. The locus of control in this legal relationship is focused on the subject exercising its rights and fulfilling its obligations. In legal validity, the legal relationship is due to the intentionality of the legal consciousness of the subject to implement legal norms through legal interaction with other participants in the legal relationship. The normativity of legal reality is based on legal regulation through legal acts (individual and general). In such a legal relationship, the subjects exercise their legal capabilities to the fulfillment of the legal duties assigned to other subjects. The locus of control is shifted to other participants in the legal relationship who exercise their rights and perform legal duties. In legal interaction, mutual recognition of the right is provided by the instance and/or the party of the legal relationship. In the legal validity, the physical, social and value, as well as vital normativity are supplemented by legal normativity. It is designed to neutralize social contradictions caused by the limitations of space, as well as the irreversibility of time. It is proved that the proposed concept of legal relations contributes to the solution of practical issues of the primacy of the legal norm or legal relationship, the revision of the criteria for differentiation of the legal system, the determination of the ratio of legal relations and offenses, the scientific consideration of some sectoral problems of the classification of legal relations. It is noted that the proposed concept of a legal relationship as a social action or legal interaction is quite conditional and applicable for cognitive purposes. In practice, quite often there is an intersection or mutual overlap of one type with another, a transition from legal reality to legal reality.